The Resistance Resistance to the Dutch Colonizers in the Novel Tambera The work of Utuy Tatang Sontani - Dianti, Nila; Doyin, Mukh; Styaningsih, Nas Haryati (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
The novel Tambera by Utuy Tatang Sontani is a postcolonial novel. The story is set during the Dutch colonial period in the community of Banda Neira. This research utilizes a postcolonial approach and then dissects it using James Scoot's theory of resistance. The problem formulations studied are open and closed forms of resistance. Based on this research question, the aim of this research is to find forms of community resistance to the Dutch and the causes of community resistance to the Dutch in the novel Tambera by Utuy Tatang Sontani. In the novel Tambera by Utuy Tatang Sontani, there are 10 findings that caused resistance: (1) Wubani's opinion that the Dutch brought harm, (2) the kawista were angry, (3) the Maruko family became the topic of discussion for Imbata and his friends, (4) the kawista protested against construction of Fort, (5) kawista incited the residents who built the Fort, (6) nutmeg sale and purchase contract, (7) rejection of the nutmeg sale and purchase contract, (8) Tambera was annoyed with Imbata, (9) Wubani was suspicious of the presence of the Dutch army, (10) Gapipo's annoyance regarding nutmeg sales and purchase contracts and weapons searches. Benefits for an academic perspective, this research will produce a thesis on resistance as a theoretical contribution to the development of Indonesian language and literature education studies, especially regarding James C. Scoot's theory of resistance. Researchers hope that the results of this research will contribute to lecturers and teachers as teaching material in the development of literary science.